Potential Of Jicama as A Synbiotic Product For Stunted Children: A Narrative Literature Review - Amellia A'isyti Zen Arjaeni Malik; Rini Harianti (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
Stunting is a chronic nutritional problem associated not only with inadequate nutrient intake but also with imbalances in gut microbiota and digestive tract disorders. One potential strategy to improve this condition is the development of synbiotic beverages based on local food sources, such as jicama (Pachyrhizus erosus), which contains natural prebiotics, including inulin and fructooligosaccharides (FOS). This study aimed to examine the potential of jicama as a prebiotic source in the development of synbiotic beverages for stunted children. This study employed a narrative literature review method through article searches in PubMed/NCBI, ResearchGate, Taylor & Francis, MDPI, and Google Scholar databases. The keywords used included “stunting,” “gut microbiota,” “synbiotic,” “prebiotic,” and “jicama.” Articles published between 2016 and 2026 were selected based on inclusion and exclusion criteria. The review results showed that jicama contains oligosaccharides, inulin, and fructooligosaccharides (FOS) that have the potential to enhance the growth of lactic acid bacteria and support the production of short-chain fatty acids (SCFA). In addition, a synbiotics product may help improve gut microbiota balance and digestive health in stunted children. In conclusion, jicama has the potential to be developed as a functional synbiotic beverage ingredient to support improvements in digestive health in stunted children.